2022
DOI: 10.3390/jcm11071822
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vaccination against COVID-19 in Chronic Spontaneous and Inducible Urticaria (CSU/CIU) Patients: A Monocentric Study

Abstract: Background: Patients affected by pre-existing chronic spontaneous/Inducible urticaria (CSU/CIU) still feel unsafe due to the potential risk of an Adverse Event Following Immunization (AEFI) and Cutaneous Adverse Reactions (CARs) of COVID-19 vaccines. The appropriate management in this field remains debated and evidence is still lacking. Methods: We considered 160 CSU/CIU patients in Omalizumab/antihistamine therapy who received two doses of Comirnaty/Moderna mRNA vaccines; 20 of them also received a booster do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Another recent study carried out on adult patients is in line with our data, as the relapse rate of CU after the first vaccine dose is very similar to ours (8.12%), and the average duration of relapse is less than 7 days (2 days and 11 hours). 30 Two similar adult-onset cases were described in a study in which patients with a history of CSU experienced a relapse of urticaria after the first dose of the COVID-19 vaccine. 31 On comparing the percentage of patients with CSU relapse or worsening after COVID-19 (19.2%) with the percentage of patients with CSU relapse or worsening after COVID-19 vaccination (7.7%), quite similar results were obtained.…”
Section: Discussionmentioning
confidence: 85%
“…Another recent study carried out on adult patients is in line with our data, as the relapse rate of CU after the first vaccine dose is very similar to ours (8.12%), and the average duration of relapse is less than 7 days (2 days and 11 hours). 30 Two similar adult-onset cases were described in a study in which patients with a history of CSU experienced a relapse of urticaria after the first dose of the COVID-19 vaccine. 31 On comparing the percentage of patients with CSU relapse or worsening after COVID-19 (19.2%) with the percentage of patients with CSU relapse or worsening after COVID-19 vaccination (7.7%), quite similar results were obtained.…”
Section: Discussionmentioning
confidence: 85%
“…The rate of allergic reactions to Pfizer-BioNTech vaccine is higher among patients with allergies, particularly among a subgroup with a history of high-risk allergies. The literature suggests that most patients with a history of allergic diseases and, particularly, highly allergic patients can be safely immunized at certain medical facilities and/or referral centers after completing a risk assessment questionnaire [6]. Further studies are required to define more specific risk factors predisposing to Type I hypersensitivity to COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…A careful analysis of the reported cases of severe allergic reaction to vaccines has shown that they are very rare and mostly related to certain ingredients, such as polyethylene glycol and polysorbate, which are used as excipients [3]. The most frequently reported cutaneous manifestations that present after more than 24 h after the vaccine include the "COVID arm", or the onset of sometimes erythematous, painful patches, located at the injection site; urticaria-like skin reactions; exanthema-like eruptions, erythema multiforme, erythematous lesions in the lower limbs, pityriasis rosea, lymphomatoid drug reactions and flare up of psoriasis [1,[4][5][6]. Herein, we aim to describe cases of patients referred to our outpatient clinic with cutaneous manifestations following COVID-19 vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published study similarly reported that 92% of 160 CSU patients did not experience a relapse in symptoms after vaccination against COVID‐19. 5 However, our results may be limited owing to the small sample size, and most of our patients had only mild CSU activity. In conclusion, we have demonstrated that the mRNA COVID‐19 vaccine does not induce flares of mild to moderate severity CSU (UAS7 ≤27).…”
mentioning
confidence: 81%